Afadin Downregulation by Helicobacter pylori Induces Epithelial to Mesenchymal Transition in Gastric Cells - Marques, Miguel Sardinha; Melo, Joana; Cavadas, Bruno; Mendes, Nuno; Pereira, Luísa; Carneiro, Fátima; Figueiredo, Ceu; Leite, Marina (Frontiers in Microbiology, 2018)
Afadin is a cytoplasmic protein of the adherens junctions, which regulates the formation and stabilization of both the adherens and the tight junctions. Aberrant expression of Afadin has been shown in cancer and its loss has been associated with epithelial to mesenchymal transition (EMT). EMT is characterized by the change from an epithelial to a mesenchymal phenotype, with modifications on the expression of adhesion molecules and acquisition of a migratory and invasive cell behavior. While it is known that Helicobacter pylori disrupts the tight and the adherens junctions and induces EMT, the effect of the bacteria on Afadin is still unknown. The aim of this study was to disclose the effect of H. pylori on Afadin and its impact in the induction of an EMT phenotype in gastric cells. Using two different cell lines, we observed that H. pylori infection decreased Afadin protein levels, independently of CagA, T4SS, and VacA virulence factors. H. pylori infection of cell lines recapitulated several EMT features, displacing and downregulation multiple proteins from cell-cell junctions, and increasing the expression of ZEB1, Vimentin, Slug, N-cadherin, and Snail. Silencing of Afadin by RNAi promoted delocalization of junctional proteins from the cell-cell contacts, increased paracellular permeability, and decreased transepithelial electrical resistance, all compatible with impaired junctional integrity. Afadin silencing also led to increased expression of the EMT marker Snail, and to the formation of actin stress fibers, together with increased cell motility and invasion. Finally, and in line with our in vitro data, the gastric mucosa of individuals infected with H. pylori showed decrease/loss of Afadin membrane staining at cell-cell contacts significantly more frequently than uninfected individuals. In conclusion, Afadin is downregulated by H. pylori infection in vitro and in vivo, and its downregulation leads to the emergence of EMT and to the acquisition of an aggressive phenotype in gastric cells, which can contribute to gastric carcinogenesis.